Grain yield and quality of wheat are improved through post-flowering foliar application of zinc and 6- benzylaminopurine under water deficit condition - Zarea, Mohammad Javad; Karimi, Nasrin (Frontiers in Plant Science, 2023)
Introduction Zinc (Zn) as an essential micronutrient and cytokinin as phytohormone not only regulate plant growth but also play fundamental roles in plant tolerance against drought stress. Understating the function and the role of cytokinin in combined with an essential micronutrient, Zn, could improve the choice of a sustainable strategy for improvement of plant drought stress. The objective of this field research was to determine the effect of post-flowering foliar application of ZnSO4 and 6-benzylaminopurine (6-BAP) on grain yield and quality of winter wheat under water deficit condition. Methods Experiments were conducted under filed condition. Drought was imposed by with holding irrigation at the beginning of flowering till the signs of temporary wilting/leaf rolling appeared, after which all plots were irrigated to field capacity. The foliar treatment consisted of (1) foliar application of water, as control treatment; (2) foliar application of 10 g ha-1 6-BAP; (3) Foliar application of 20 g ha-1 6-BAP; (4) Foliar application of 10 g ha-1 6-BAP plus foliar application of 6 kg ha-1 ZnSO4 solution and (5) foliar application of 10 g ha-1 6-BAP plus foliar application of 6 kg ha-1 ZnSO4 solution 2 days before drought imposition. Data were collected on grain and straw yield, yield attributes, harvest index, flag leaf fresh matter and dry matter weight, TaCKX6-D1 expression, phytic acid content in grains, mycorrhiza colonization rate and succinate dehydrogenase (SD) activity. Results According to ANOVA, the factor ‘Zn’ significantly affected leaf relative water content (p < 0.001). Relative water content for plants foliar applied with 6-BAP was not statistically significant. Applying Zn increased yield, straw dry weight, and kernel weight relative to plants sprayed with water alone. Increased grain yield due to foliar application of Zn was associated with decrease in cytokinin oxidase/dehydrogenase (TaCKX) and increase in kernel weight. Results showed that the drought stress significantly decreased 1000-grain weight that was accompanied with over-expression of cytokinin oxidase/dehydrogenase (TaCKX). Foliar application of Zn increased the concentration of Zn in grains. The experimental data on the zinc content of grain indicated no significant difference between the 6-BAP at 10 mg L-1 and control treatment. The phytate to Zn molar ratio was significantly affected by foliar applied Zn, but not significantly by applied 6-BAP. In the present study, SD activity of the hyphae of indigenous arbuscular mycorrhizal fungi (IAMF) associated with plant roots was also assayed. Results disclose that SD activity of IAMF was significantly affected by Zn treatments during grain filling stages. Discussion In summary, both foliar applied Zn and 6-BAP had the significant effects on all measured parameters in winter wheat. However, spike number, harvest index and mycorrhizal colonization rate were neither significantly affected by Zn nor 6- BAP. Foliar application of Zn at 0.6% (6 kg ha-1) and higher 6-BAP (20 mg L-1 m-2) promoted wheat growth and performances under imposed drought stress condition. Plant that only foliar sprayed with water showed higher level of TaCKX6-D1 expression as compared to Zn treated plants, indicating these plants were more affected by imposed drought relative to those plants treated with Zn. The results of this study provides evidence that a combination of Zn and 6-BAP could be an effective in improvement of drought tolerance of wheat and prevents grain yield from further reduction in terms of quality and quantity due to drought stress.